A detailed appraisal of mesocolic lymphangiology – an immunohistochemical and stereological analysis. Issue 4 (19th July 2014) - Culligan, Kevin; Sehgal, Rishabh; Mulligan, Daniel; Dunne, Colum; Walsh, Stewart; Quondamatteo, Fabio; Dockery, Peter; Coffey, J. Calvin
Abstract Inadequate resection of the adjoining mesentery is associated with adverse outcome for colon cancer. Disruption of the integrity of the mesenteric lymphatic package has been implicated in this, though not proven. Recent studies have determined mesenteric anatomy and histology and now provide an opportunity to determine accurately the distribution of lymphatic vessels. The aim of this study was to characterise the distribution of the lymphatic vessels (LV) within the small intestinal and colonic mesentery, and in Toldt's fascia, which lies between the mesocolon and underlying retroperitoneum. Mesenteric samples were harvested from 12 human cadavers. Samples were taken from the small bowel mesentery, ascending, transverse, descending mesocolon and from both apposed and non‐apposed portions of the mesosigmoid. Serial sections were stained immunohistochemically with monoclonal antibody D2‐40 (podoplanin), and Masson's Trichrome. Lymphatic vessel (LV) density and radius of diffusion were determined using a stereological approach. A lymphatic network was embedded within the mesenteric connective tissue lattice throughout each mesenteric region. LV were identifiable within the submesothelial connective tissue where they measured 10.2 ± 4.1 μm in diameter and had an average radius of diffusion of 174.72 ± 97.68 μm. Unexpectedly, LV were identified in Toldt's fascia, where they measured 4.3 ± 3.1 μm in diameter and had a radius of diffusion of 165.12 ± 66.26 μm. This is the first study systematically to determine and quantify the distribution of lymphatic vessels within the mesenteric organ and to demonstrate the presence of such vessels within Toldt's fascia. A rich lymphatic network occupies all levels of the mesenteric connective tissue lattice. Within the latter, they are found within 0.1 mm of peritonealised mesenteric surfaces and are separated by an average distance of 0.17 mm and may be particularly vulnerable during surgery.